Evaluation of the Fertility Status of Irrigated Rice Fields in Relation to Rice Productivity (Oryza Sativa L.) in Debowae Village, Waelata District, Buru Regency, Maluku Province - Talakua, Jemelin M; Kaya, Elizabeth; Habi, M La; Talakua, S M (Jurnal Agroekoteknologi, 2024)
ABSTRACTThis research examines the fertility status of irrigated rice fields in Debowae Village, Waelata District, Buru Regency, using a survey method for field work, taking composite soil samples diagonally in rice fields based on the history of fertilizer use and production data through interviews. The results of the research show that the fertility status of paddy fields in Debowae village based on chemical characteristics is low status with limiting factors including acid soil pH (5.29-5.51) to slightly acidic (5.80-5.89), low CEC (5.28-8.21me/ 100gram), C-organic low (0.53%) to low (1.17-1.67%) and N- low (0.18-0.20%) to moderate (0.21-0.24%). This had an effect on decreasing GKG production at the research location, namely 2.5-4.5 tons/ha, which means it is still relatively low when compared to national GKG production, namely 5.4 tons/ha. Therefore, the direction for balanced fertilizer management is based on the soil fertility status of the paddy fields at the research location, namely adding lime to increase soil pH, using organic material to increase soil C-organic and soil CEC, as well as using compound fertilizer using a combination of urea, NPK fertilizers. Ponska in supporting sustainable agricultural land. Key words: Soil fertility status, rice production, balanced fertilization.